Sistem Pakar Diagnosa Hipertiroid Menggunakan Certainty Factor dan Logika Fuzzy - Rizkita Apriliana; Auli Damayanti; Asri Bekti Pratiwi (Universitas Airlangga, 2020)
Hyperthyroidism is a condition when the function of thyroid gland becomes excessive. The excess function of thyroid gland increases thyroid hormone production which affect body metabolism and physiological activity. This study aims to make an expert system diagnose hyperthyroidism with certainty factor and fuzzy logic. The stages of the process of diagnosing hyperthyroidism including problem identification, needs analysis of symptoms and types of hyperthyroidism, determination of rules, system design, case examples implementation, system testing, and evaluation. Variables used were systolic blood pressure, triiodothyronine (T3) levels, thyroxine (T4) levels, thyroid stimulating hormones (TSH) levels, goiter, tremors, and excessive sweating. All variables are processed using fuzzy logic with fuzzyfication stages, rule determination, min implications, max rule composition, and defuzzyfication which then proceed with certainty factor with sequential CF and CF stages. The system output is diagnosis the condition of hyperthyroidism such as hyperthyroidism, subclinical hyperthyroidism, and normal accompanied by a certainty factor. Based on the evaluation result, the accuracy of the expert system according to expert diagnostics is 86.7%